Synchronizing a triple dragline stripping system in thick overburden - Erdem, Bülent; Özkan, İhsan; Duran, Zekeriya (GeoScience Engineering, 2017)
This study addresses the use of combined stripping systems to investigate the technical feasibility of extracting thick coal seams underlying deep overburden strata. The possibility of using multiple draglines in tandem with bucket wheel excavator systems is explored. Pit geometry design alternatives incorporating a triple dragline excavation fleet with bucket wheel excavator-cross pit spreader sub-systems (BWE+XPS) are examined. A production simulation algorithm, which emphasizes synchronizing excavator units in the triple dragline system, is developed. The combined methodology is evaluated on Sector-D of the Afşin-Elbistan lignite basin, one of the most important resources for electricity production in Turkey. The results reveal that a combined stripping fleet may successfully perform overburden stripping at the predetermined rate and uncover coal seams.